Accounting for sustainability and social responsibility - Reizinger-Ducsai, Anita (Research Papers of Wrocław University of Economics, 2018)
In this paper the issue of environmental and social responsibility is considered. I look into the goals that sustainability reports and social responsibility reports can serve and how they can draw attention to creating shared value. My research areas include the measurement of financial performance and the methodology for the comparability of conclusions from accounting reports. Some questions arise when this is completed with sustainability reports: how can sustainability performance be presented; is there a way to develop a single indicator system for measuring sustainability and social responsibility? As another issue, I also focus on the ethical behaviour of companies and its impacts on profit and profitability
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515; s. 185-196
Keywords: sustainability accounting; environmental accounting; CSR; CSV; rachunkowość zrównoważona; rachunkowość środowiskowa